2000
DOI: 10.1002/1521-3773(20001215)39:24<4414::aid-anie4414>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

New Applications of Polyfunctional Organometallic Compounds in Organic Synthesis

Abstract: In the second half of the twentieth century much effort was invested in the preparation of highly reactive polar organometallic reagents. The high reactivity of these reagents precluded the presence of many functional groups and often good chemoselectivities and stereoselectivities could only by achieved by transmetalation reactions. The synthesis of increasingly complex target molecules and the desire to avoid tedious protection-deprotection steps has led inevitably to the use of functionalized organometallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 0 publications
0
31
0
3
Order By: Relevance
“…Knochel et al have reported the halogen-magnesium exchange for the preparation of polyfunctional organomagnesium reagents. 60,61 Aryl, heteroaryl, and alkenyl halides bearing electron-withdrawing groups or metal-directing groups can be converted into the corresponding magnesium reagents by treating with i-PrMgBr or i-Pr 2 Mg in THF at low temperatures. However, substrates are often limited to rather electron-poor aryl or alkenyl halides, particularly in the case of bromides.…”
Section: 59mentioning
confidence: 99%
“…Knochel et al have reported the halogen-magnesium exchange for the preparation of polyfunctional organomagnesium reagents. 60,61 Aryl, heteroaryl, and alkenyl halides bearing electron-withdrawing groups or metal-directing groups can be converted into the corresponding magnesium reagents by treating with i-PrMgBr or i-Pr 2 Mg in THF at low temperatures. However, substrates are often limited to rather electron-poor aryl or alkenyl halides, particularly in the case of bromides.…”
Section: 59mentioning
confidence: 99%
“…Concerning the second point, we have been interested in the last several years in the study of functionalized organometallic compounds because in their reaction with electrophiles they are able to yield polyfunctionalized molecules in only one reaction step [3]. Among the different possibilities, we have studied mainly functionalized organolithium intermediates due to their high reactivity, even at low temperatures, based on the high polarity of the carbon-lithium bond [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Organolithium compounds constitute a unique class of reagents due to their characteristic reactivity, the functionalized organolithiums and the polylithium synthons being of special interest in organic synthesis. [4][5][6][7][8][9][10][11][12][13][14][15] Deprotonation and halogen/lithium exchange, employing commercially available organolithium reagents, are conventionally the main routes for the preparation of other organolithium reagents.…”
Section: Introductionmentioning
confidence: 99%